ESP32-CAM Camera Integration and Android Control for Portable Real-Time Surveillance Solution - Zulhipni Reno Saputra Elsi; Dedi Haryanto; Muhammad Ihsan (Progresif: Jurnal Ilmiah Komputer, 2025)
The development of Internet of Things (IoT) technology has encouraged the creation of a more flexible and efficient intelligent surveillance system. This research aims to design and implement an ESP32-CAM-based surveillance car prototype capable of real-time visual monitoring via Wi-Fi connection. The system integrates an ESP32-CAM microcontroller, an L298N motor driver, and four DC motors, and is controlled through a specially developed Android application to set the direction of motion and receive live video displays from the camera. Test results show that the system has stable connectivity performance with an average delay of 0.88 seconds, motor control response of 0.48 seconds, and good quality video streaming with an average delay of 1.09 seconds. The effective operational range was recorded up to 30 meters with acceptable connection quality. The system shows potential as a cost-effective, portable, and easily accessible surveillance solution for applications in hard-to-reach or high-risk areas. This research opens up further development opportunities with the integration of artificial intelligence, additional sensors, as well as expansion of the communication range.Keywords: IoT; ESP32-CAM; Real-Time Surveillance; Surveillance RC Car; Video Streaming AbstrakPerkembangan teknologi Internet of Things (IoT) telah mendorong terciptanya sistem pengawasan cerdas yang lebih fleksibel dan efisien. Penelitian ini bertujuan untuk merancang dan mengimplementasikan prototipe mobil pengawasan berbasis ESP32-CAM yang mampu melakukan pemantauan visual secara real-time melalui koneksi Wi-Fi. Sistem ini mengintegrasikan mikrokontroler ESP32-CAM, driver motor L298N, dan empat motor DC, serta dikendalikan melalui aplikasi Android yang dikembangkan khusus untuk mengatur arah gerak dan menerima tampilan video langsung dari kamera. Hasil pengujian menunjukkan bahwa sistem memiliki performa konektivitas yang stabil dengan rata-rata delay 0,88 detik, respons kendali motor sebesar 0,48 detik, dan streaming video berkualitas baik dengan delay rata-rata 1,09 detik. Jangkauan operasional efektif tercatat hingga 30 Meter dengan kualitas koneksi yang masih dapat diterima. Sistem ini menunjukkan potensi sebagai solusi pengawasan yang hemat biaya, portabel, dan mudah diakses untuk aplikasi di area yang sulit dijangkau atau berisiko tinggi. Penelitian ini membuka peluang pengembangan lebih lanjut dengan integrasi kecerdasan buatan, sensor tambahan, serta perluasan jangkauan komunikasi.Kata kunci: IoT; ESP32-CAM; Pengawasan Real-Time; Mobil RC Pengintai; Streaming Video